1959
DOI: 10.1139/v59-083
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations on the Theory of Dielectric Relaxation in Associated Liquids

Abstract: The theory of a b s o l~~t e rcaction rates is esamined for the case of relasation it1 associated polar liquids where the activatiori process is probably an excitation of a librational motion to one of complete rotation over a rotatioilal potential energy barrier. The rotational barriers in water are calculated using the point-charge model of the water quadrupole and the eifect of thermal bond bending is csamiiied. The esperiineiital heats of activation for dielectric relaxation in water and deuterium oside ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Thus Conway30 calculated that (H*d»o-H*h2o) for dielectric relaxation was 300 cal. and a similar value was to be expected31 and was found for vis-cosity32 based on data of Harday and Cottingdon.6 In both calculations, AH* was found to decrease with rising temperature with a coefficient of about - 30 cal./deg. Since structural stability as used here is the physical consequence of the difference between structure forming from dipole-dipole interaction and the structure breaking of thermal activation; as the latter increases the residual must decrease both absolutely and differentially as between H20 and D20 whatever model of water we choose to adopt.…”
supporting
confidence: 88%
“…Thus Conway30 calculated that (H*d»o-H*h2o) for dielectric relaxation was 300 cal. and a similar value was to be expected31 and was found for vis-cosity32 based on data of Harday and Cottingdon.6 In both calculations, AH* was found to decrease with rising temperature with a coefficient of about - 30 cal./deg. Since structural stability as used here is the physical consequence of the difference between structure forming from dipole-dipole interaction and the structure breaking of thermal activation; as the latter increases the residual must decrease both absolutely and differentially as between H20 and D20 whatever model of water we choose to adopt.…”
supporting
confidence: 88%
“…Phillips and co-workers (27) have determined that the heat capacity transfer functions become increasingly positive as the alkyl chain length increases in these salts. Conway (28) previously demonstrated that this was consistent with the increasing tendency for solvent restructuring caused by interactions with the cation alkyl chains.…”
Section: Resultssupporting
confidence: 61%
“…3), in agreement with previous findings. 39,42,45,57 This deviation indicates that DH # and DS # are temperature-dependent, which can be accounted for by the isobaric heat capacity of activation, Dc p # : 39,57 O is more structured than H 2 16 O. 5,19,20,23,24 Overall, our results indicate that an increase in t c upon H/D substitution arises predominantly from the higher DH # (D…”
Section: The Effect Of Temperature On the Relaxation Time Of The Cooperative Modementioning
confidence: 73%